Characterization of A Mixed Tea Formulation of Mangosteen Peel, Cinnamon, and Clover - Rahmawati Rahmawati; Yunita Satya Pratiwi; Yushinta Aristina Sanjaya; Tania Amalia (Universitas Darussalam Gontor, 2024)
Herbal tea is an infusion of various leaves, roots or flowers that is not derived from the Camellia sinensis L. The combination of mangosteen peel, cinnamon, and cloves can be used as an alternative to develop products in the form of herbal tea drinks because it has high antioxidant activity. This study aimed to evaluate the composition and toxicity aspects of various tea formulations mixed with mangosteen peel, cinnamon, and cloves. The research methodology inlcuded the measurement of water content and crude fiber with the AOAC method, alkalinity based on ISO 1758, and toxicity tests with the Brine Shrimp Lethality Test (BSLT) method. The data obtained were analyzed with ANOVA test and Tukey post hoc test (p < 0.05 and Î± = 0.05.) The results of the analysis showed that all herbal tea formulations tested had water content in the range of 10.34%-11.52%, crude fiber in the range of 15.12-16.84%, and alkalinity in the range of 1.19%-1.31%. The quality parameters of tea mixture of mangosteen peel, cinnamon and cloves compared to the Indonesian National Standard (SNI) 01-3836-2013 generally revealed a significant impact (p < 0.05 and Î± = 0.05). Based on toxicity tests, this tea is categorized as non-toxic because it has an LC50 value of 6307.48 ppm